If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9n + -29 = 2nforp Reorder the terms: -29 + 9n = 2nforp Solving -29 + 9n = 2fnopr Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2fnopr' to each side of the equation. -29 + -2fnopr + 9n = 2fnopr + -2fnopr Combine like terms: 2fnopr + -2fnopr = 0 -29 + -2fnopr + 9n = 0 Add '29' to each side of the equation. -29 + -2fnopr + 29 + 9n = 0 + 29 Reorder the terms: -29 + 29 + -2fnopr + 9n = 0 + 29 Combine like terms: -29 + 29 = 0 0 + -2fnopr + 9n = 0 + 29 -2fnopr + 9n = 0 + 29 Combine like terms: 0 + 29 = 29 -2fnopr + 9n = 29 Reorder the terms: -29 + -2fnopr + 9n = 29 + -29 Combine like terms: 29 + -29 = 0 -29 + -2fnopr + 9n = 0 The solution to this equation could not be determined.
| 5(-6+9x)-4= | | 4x=1x+12 | | 5v+1=8+6v | | -13+3x=7-x | | -3(x)=-2x-1 | | x(x-4)=x+3x+5 | | 4a-13=a+4 | | 10x+10=9x-9 | | 4a^3b-4b^4=0 | | 9x^2+4y^2+36z^2=36 | | 6-3r=1+2r+1+4 | | abs(x+5)-2=12 | | -4+7(4+9)=35 | | 10v=18+v | | 31-3x=20+8x | | a-5=-5+4a | | 2x-5.74=-4.46 | | 12x+8=5x+22 | | -w+17=20 | | 10x+5=5x-4 | | 4(3d-7)=32 | | m+kg+2=j | | f(x)=12x-1 | | y+7=-2(x-4) | | 9X^2-9X+7=0 | | 5xy=8 | | -x=-9/4 | | 4x+41=13x-94 | | 15+2(3x-6)= | | 2x-12=-6x+4 | | 3h+64m+7h-4m= | | y=13(3x+2) |